PERAN KEPUASAN KERJA MEMEDIASI PENGARUH PSYCHOLOGICAL CONTRACT TERHADAP TURNOVER INTENTION KARYAWAN - Suryadewi, Ni Putu Diah; Surya, Ida Bagus Ketut (E-Jurnal Manajemen; Vol 9 No 5 (2020)DO - 10.24843/EJMUNUD.2020.v09.i05.p04, 2020)
The purpose of this study was to determine the Effect of Job Satisfaction Mediating Psychological Contracts on Turnover Intention. This research was conducted at The Samaya Ubud Luxury Villas. The number of samples in this study were 58 employees in the housekeeping department, especially saturated sampling. Data collection was carried out by interview and questionnaire. The analysis technique used is path analysis. Based on the results of the analysis shows that psychological contract has a negative and significant effect on turnover intention, job satisfaction has a negative and significant effect on turnover intention, psychological contract has a positive and significant effect on job satisfaction, and job satisfaction partially mediates psychological contract on turnover intention in housekeeping department employees The Samaya Ubud Luxury Villas. Keywords: psychological contract, job satisfaction, turnover intention